Deforestation and property rights: A comparison between former British and Spanish colonies - David Corderí Novoa (Colegio de Economistas de A Coru\~na, 2008)
According to the United Nations Food and Agriculture Organization changes in the land use of many developing countries have resulted into a rapid process of deforestation in tropical areas during the 80s and 90s. The impact of insecure ownership and badly defined property rights on deforestation has been extensively studied. It is argued that open access resources are typically subject to a more than optimal extraction rate, which is also known as 'The Tragedy of the Commons.' This paper first explains how institutions such as property rights have influenced land use. Then, the paper compares the British and Spanish colonial systems in terms of property rights and their different impact on forest management. Finally, the paper concludes that, according to the empirical results, stronger property rights encourage less deforestation controlling for a number of variables. At the same time, the empirical evidence suggests that former British colonies do relatively better than former Spanish in terms of avoiding deforestation.
Keywords: 330